Training on the Utilization of Household Organic Waste for Tourism Nagari Silokek Residents as Ecoenzyme - Resti - Fevria; Vauzia Vauzia (Pelita Eksakta, 2023)
Household organic waste is one of the largest contributors to waste in Indonesia. Various efforts have been made to reduce this waste so that over time it does not accumulate and endanger the environment. One way to process this organic waste is to process it into ecoenzymes. ecoenzyme is a fermented liquid from fruit or vegetable skin mixed with sugar. ecoenzyme has many benefits for households because it has the ability to act as an antimicrobial agent and can also be used as a cleaning fluid. In this service, educational activities regarding the manufacture of ecoenzymes were carried out for the people of Nagari Silokek Sijunjung. After delivering the material to the participants, it was discovered that the participants in this activity had the ability to make ecoenzymes in the community environment.